Un detail immense. - Palais des Beaux-Arts, Charleroi (Charleroi : Palais des Beaux-Arts, 1991)
Saint François d'Assise ; Evenepoel, Henri ; Fabre, Jean-Henri ; Kawara, On ; Anselmo, Giovanni ; Morandi, Giorgio ; De Cordier, Thierry ; Darboven, Hanne ; Tahara, Keiichi ; François, Michel ; Laib, Wolfgang
Un detail immense, Palais des Beaux-Arts, Charleroi, du 16 mars au 5 mai 1991
boek